Growth performance, haematological and biochemical responses of Nile tilapia Oreochromis niloticus fed graded levels of groundnut cake - Ayoola, Simeon Oluwatoyin; Kolawole, Ayotunde Samuel; Etim, Faith (Aceh Journal of Animal Science, 2023)
The assessment of the effect of replacing fish meal with groundnut cake in the diet of Nile tilapiaOreochromis niloticuswas carried out in a twelve-week feeding trial. The objective of the study was to determine the appropriate level of groundnut cake inclusion in fish feed diet. Ten Nile tilapia fingerlings with mean weight of 7.550.50g were stocked in experimental tanks in triplicate. Varying levels of groundnut cake were incorporated in the experimental diets formulated; the control diet, Diet 0, 1, 2, 3, 4 and 5 having 0%, 20%, 40%, 60%, 80% and 100% inclusion level respectively. The experimental diet five exhibited the highest mean weight gain (8.001.68) and specific growth rate. But recorded the least significant feed conversion ratio (4.011.10). The diet also recorded the best protein efficiency ratio (1.370.30). There was significant difference observed in the growth performance, haematological values and biochemical values in fish fed with groundnut cake compared to the control diet. A reduction in the cholesterol (1.660.13) and Albumin (40.201.10) values were observed in fish fed groundnut cake based diet compared with the fish fed with the control diet having cholesterol and albumin values to be1.830.07 and40.601.60 respectively. It was observed that the use of groundnut cake in fish feed forO. niloticusenhances the growth of the fish. The 100% substitution shows highest weight gain, low FCR and low level of cholesterol.In conclusion, 80% partial replacement of fish meal in fish feed with groundnut cake should be encouraged.